THE IMPORTANCE OF SPITEFULNESS IN THE ECONOMIC ANALYSIS OF LITIGATION - Mojašević, Aleksandar; Radulovic, Branko (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The subject of this paper is spitefulness, as a notion and special social preference, and spiteful behavior. The goal is to examine the significance of the spitefulness and its implications in analyzing the litigation and the choice between trial and settlement. In this paper, spitefulness is viewed from the perspective of different economic science' disciplines (behavioral economics, experimental economics, neoclassical economic analysis of law), but also psychology and evolutionary biology. Yet, the primacy is given to behavioral economics point of view, from which the spitefulness is defined as a willingness to inflict harm on others at one's costs. Also, the paper presents statistics on the number of civil proceedings in Serbia, together with comparative data, and discusses the implications of spitefulness and spiteful behavior on the number of civil proceedings. The paper sets out a conceptual framework for further empirical research on spite and spiteful behavior and their importance in deciding whether to initiate litigation and/or choose between trial and settlement to answer the question of whether Serbian citizens prefer to litigate and what is the role of spite in that.
Keywords: spite; spiteful conduct; litigation; settlement; economic analysis